(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Chatbots have become very popular in our times and are used in several fields. The emergence of chatbots has created a new way of communicating between human and computer interaction. In this study, we have developed a Chatbot in Arabic language, which is a program that can understand and analyze Arabic language. The Chatbot developed in this study contributes to its users about the Prophet’s biography and provide them with valuable information. SeerahBot will be the first chatbot dedicated to the Prophet’s biography. We implemented this system by using two methods first build retrieval based chatbot from scratch using natural language processing NLP and machine learning techniques and second technique we used a chatbot design platform. To facilitate access to SeerahBot, we have made it available on Telegram. SeerahBot was tested, and the results were acceptable.